Analyzing the Impact of Heuristic Biases on Investment Decisions Through Risk Tolerance: Evidence from Generation Z Investors in Indonesia - Stievanie; Bertha Silvia Sutejo; Liliana Inggrit Wijaya (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
This study aims to examine the influence of heuristic biases, specifically overconfidence bias, availability bias, and representativeness bias on investment decisions among Generation Z investors in Indonesia, with risk tolerance serving as a mediating variable. The research replicates and extends previous models by incorporating representativeness bias into the framework. Using a quantitative approach, data were collected through an online questionnaire distributed to 208 respondents who met the specified sampling criteria. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicate that availability bias, representativeness bias, and risk tolerance have a significant positive effect on investment decisions, while overconfidence bias does not directly influence them. Additionally, overconfidence bias, availability bias, and representativeness bias significantly affect risk tolerance. The mediation analysis shows that risk tolerance mediates the relationship between availability bias and representativeness bias with investment decisions, but does not mediate the relationship between overconfidence bias and investment decisions. These findings highlight the significant role of cognitive biases and risk tolerance in shaping the investment behavior of Generation Z investors in Indonesia. The study contributes to behavioral finance literature by providing evidence on how psychological factors and cognitive tendencies influence financial decision making.